Social Identity Correlates of Minority Workers' Health - James, Keith; Lovato, Chris Y.; Khoo, Gillian (Academy of Management Journal, 1994)
A study of how minority workers' social relationships at work and social-behavioral tendencies influence their health is reported. We observed significant correlates for both blood pressure and self-reports of health. Theoretical, methodological, and applied implications of the results are discussed.